The Effects of School Finance Reforms on Teacher Salary and Turnover: Evidence from National Data - Tuan D. Nguyen; J. Cameron Anglum; Michael Crouch (AERA Open, 2023)
In recent decades, parallel literature has documented the magnitudes and effects of teacher turnover and the impact of state school finance reforms (SFRs). In this paper, we examine SFRs as possible mechanisms to improve teacher salary, turnover, and job satisfaction by using nationally representative data from 2000 to 2016 and leveraging variation in SFR timing. We find that SFRs increased teacher salaries by approximately $4,000 and reduced teacher turnover by three percentage points, on average, though gains in both outcome measures took up to a decade to emerge. We observe larger salary gains among teachers in high-poverty and high-minority school contexts, though declines in their corresponding turnover behaviors were similar to average findings. As policymakers seek to address heightened concerns regarding teacher retention and shortages, our findings suggest targeted salary policies may improve rates of teacher attrition.